Convalescent plasma for pediatric patients with SARS‐CoV‐2‐associated acute respiratory distress syndrome. Issue 11 (4th September 2020) - Diorio, Caroline; Anderson, Elizabeth M.; McNerney, Kevin O.; Goodwin, Eileen C.; Chase, Julie C.; Bolton, Marcus J.; Arevalo, Claudia P.; Weirick, Madison E.; Gouma, Sigrid; Vella, Laura A.; Henrickson, Sarah E.; Chiotos, Kathleen; et al.
Abstract: There are no proven safe and effective therapies for children who develop life‐threatening complications of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Convalescent plasma (CP) has demonstrated potential benefit in adults with SARS‐CoV‐2, but has theoretical risks.We present the first report of CP in children with life‐threatening coronavirus disease 2019 (COVID‐19), providing data on four pediatric patients with acute respiratory distress syndrome. We measured donor antibody levels and recipient antibody response prior to and following CP infusion. Infusion of CP was not associated with antibody‐dependent enhancement (ADE) and did not suppress endogenous antibody response. We found CP was safe and possibly efficacious. Randomized pediatric trials are needed.